Role of nebivolol in anthracycline-induced cardiotoxicity - Rudrapogu, John Satish; Govind, Biju; Unnagiri, Adinarayana (International Journal of Research in Medical Sciences, 2019)
Background: Anthracyclines are extensively used in the treatment of breast cancer. However, these therapeutic agents are responsible for chemotherapy-induced cardiotoxicity. Aim of this study was to assess the effect of use of prophylactic nebivolol for the prevention of anthracycline-induced cardiotoxicity in breast cancer patients. Methods: This was a prospective, randomized, single-blind, and placebo-controlled trial involving 80 participants with breast cancer, scheduled to undergo chemotherapy with doxorubicin. Patients were randomly divided into two groups: the nebivolol group (n=40) to receive nebivolol 5 mg daily and the placebo group (n=40) to receive placebo. All patients were evaluated with baseline Electrocardiogram (ECG) and echocardiography prior to treatment, and at the 6-month follow-up. Echocardiography included 2D echocardiography, colour doppler and tissue doppler imaging. Results: The study groups had comparable baseline echocardiographic variables. At the 6-month echocardiographic follow-up, there were no changes of statistical significance in any 2D echocardiographic variables in either group. However, there were minimal reductions of 0.4% in left ventricular ejection fraction in the nebivolol group (62.2±4.4% to 61.9±4.2%, p=0.75) and 1.6% in the placebo group (62.8±3.6% to 61.8±3.2%, p=0.18). Doppler examinations also did not reveal any statistically significant changes in variables such as peak A velocity, peak E velocity, E/A ratio, isovolumic relaxation time, and isovolemic contraction time in either group. Conclusions: Prophylactic use of nebivolol treatment may possess cardioprotective properties against anthracycline-induced cardiotoxicity in breast cancer patients although not statistically significant in this study.